2020
DOI: 10.15407/ubj92.01.092
|View full text |Cite
|
Sign up to set email alerts
|

Production and physicochemical characterization of xanthan gum by native lactose consuming isolates of Xanthomonas citri subsp. citri

Abstract: Xanthan is a biopolymer produced by Xanthomonas bacteria which is widely used in many industries such as food and oil. In this work, three Xanthomonas strains (X. citri/NIGeB-88, X. citri/NIGeB-386 and X. citri/NIGeB-K37) were used to evaluate their industrial potential to produce xanthan gum in whey medium. Bacteria growth rate, viscosity, biomass, dry weigh of produced xanthan and β-galactosidase activity were studied during the fermentation process and the presence of β-galactosidase genes was assessed by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…So, Ramezani et al showed the highest amount of produced xanthan by the X. citri NIGEB-K37 strain in a lactose-based medium (lactose 10%) to be 14.26 g/L [71]. Moravej et al (2020) increased the amount of xanthan to 18.4 g/L in the cheese whey medium without adding more lactose using the X. citri NIGEB-K37 [157].…”
Section: Bc and Xanthan Production From Wastesmentioning
confidence: 99%
“…So, Ramezani et al showed the highest amount of produced xanthan by the X. citri NIGEB-K37 strain in a lactose-based medium (lactose 10%) to be 14.26 g/L [71]. Moravej et al (2020) increased the amount of xanthan to 18.4 g/L in the cheese whey medium without adding more lactose using the X. citri NIGEB-K37 [157].…”
Section: Bc and Xanthan Production From Wastesmentioning
confidence: 99%